2014
DOI: 10.1371/journal.pone.0097515
|View full text |Cite
|
Sign up to set email alerts
|

Human Lung Epithelial Cells Contain Mycobacterium tuberculosis in a Late Endosomal Vacuole and Are Efficiently Recognized by CD8+ T Cells

Abstract: Mycobacterium tuberculosis (Mtb) is transmitted via inhalation of aerosolized particles. While alveolar macrophages are thought to play a central role in the acquisition and control of this infection, Mtb also has ample opportunity to interact with the airway epithelium. In this regard, we have recently shown that the upper airways are enriched with a population of non-classical, MR1-restricted, Mtb-reactive CD8+ T cells (MAIT cells). Additionally, we have demonstrated that Mtb-infected epithelial cells lining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 36 publications
3
104
0
4
Order By: Relevance
“…These receptors have been implicated in Mtb infection in human AECs and mediate the production of cytokines and effector molecules to mount an effective immune response. AECs play a role as immune sentinels after exposure to Mtb by presenting antigen to mucosal‐associated invariant T cells (MAITs) (Harriff et al ., 2014) and stimulating them to produce interferon (IFN)‐γ, tumour necrosis factor (TNF)‐α and granzyme, factors that may contribute to Mtb clearance. MAIT cells rapidly respond to infection, providing an early IFN‐γ boost to activate macrophages (Gold et al ., 2010).…”
Section: Cells Involved In the Innate Immune Response To Tb In Humansmentioning
confidence: 99%
“…These receptors have been implicated in Mtb infection in human AECs and mediate the production of cytokines and effector molecules to mount an effective immune response. AECs play a role as immune sentinels after exposure to Mtb by presenting antigen to mucosal‐associated invariant T cells (MAITs) (Harriff et al ., 2014) and stimulating them to produce interferon (IFN)‐γ, tumour necrosis factor (TNF)‐α and granzyme, factors that may contribute to Mtb clearance. MAIT cells rapidly respond to infection, providing an early IFN‐γ boost to activate macrophages (Gold et al ., 2010).…”
Section: Cells Involved In the Innate Immune Response To Tb In Humansmentioning
confidence: 99%
“…The increased number of IL-32-positive cells in the TB lungs reflects the large number of epithelioid macrophages in the inflammatory and granulomatous responses. Because airway epithelial cells are innate immune cells capable of killing mycobacteria through phagocytosis and elaboration of antimicrobial peptides as well as stimulating IFNγ release by CD8 + T cells (28), it is plausible that increased expression of IL-32 in these cells also reflects a host-protective immune response against MTB. Montoya et al recently showed in human macrophages that IL-32 promoted the production of both defensin-B and cathelicidin, antimicromial peptides with anti-MTB activity (29).…”
Section: Cd8mentioning
confidence: 99%
“…However, emerging evidence indicates that the cells of the innate immune system are equipped with "epigenetic memory" where genes encoding specific host defence molecules increase the response upon re-stimulation [4][5][6][7] . Recent studies further demonstrated that airway epithelial cells (AECs) harbour Mycobacterium tuberculosis (Mtb) and are critical during the progression to active disease [8,9] . These cells could thus be important for both host defence and vaccine development, but a more comprehensive knowledge of direct interaction between AECs and mycobacteria is currently lacking [10] .…”
Section: Mycobacteria Manipulate G-proteincoupled Receptors To Increamentioning
confidence: 99%